Environmental History of Rice Plantations in the Early Modern Ottoman Empire Between the 15th And 19th Centuries and Its Potential for Climate Research - Sert, Özlem (Journal of Environmental Geography, 2021)
Historians readily discuss the effect of climate change on the 21st century, but Ottomanists rarely reference palaeoclimatology data. This research compares palaeoclimatological data with documentary evidence from institutionalized rice plantations in the Ottoman Empire. Between the 15th and 19th centuries, the empire employed a group of experts for the cultivation of rice in the vast region between the Tigris and the Danube. Extensive registers exist from this period in archives that give documentary evidence about the organization of plantations, yields, prices and destructive floods. The objective of the study, as presented in this article, is to find rice-related phenological data in Ottoman Archive registers. It utilizes a comparative analysis of the Old World Drought Atlas (OWDA) summer precipitation data reconstructed by Cook et al. (2015), temperature changes, documentary evidence about seasonal extremes and archival evidence. The comparison shows that palaeoclimatology proxies are important sources of information regarding changes in rice cultivation. It also indicates that the Ottoman archive is a valuable source of possible phenological data. Thus, research sources from nature and societies complement one another. The comparison also demonstrates that climate change during the Ottoman Empire’s reign showed regional differences, and a local comparison of phenological data and palaeoclimatological data can explain more about the effects of the Little Ice Age (LIA) on the empire.